(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
PT QRS is an Indonesian pharmaceutical company that carries out the development of formulations, production, and sales of safe and quality medicines that are overseen by the official supervision and can adapt to the rapid development of health science and biotechnology. The study was conducted in the Department of Quality Control (QC) Laboratory of raw materials as one of the sub-systems of the company that was quite important in ensuring the quality of the products produced by the company. Observation results show that there are problems that often occur in the QC department that have an impact on the quality of processes in the raw material laboratory, namely the physical workload problem of raw material analysts due to several issues concerning work facilities, and the work carried out by the analyst himself. This problem causes fatigue and is overwhelmed in managing the analysis time. To overcome these problems, the analyst workload calculation is needed. The workload analysis method used is the Full-Time Equivalent method, which is time-based so that it is known how much is the burden of each analyst and the sample working time capacity that can be done by each analyst. Workload calculations are performed and the FTE values are 0.92, 1.00, 1.65, 2.19, 8.63, 0.81, and 4.53. The result shows that it is necessary to improve the number of workers in the raw material laboratory. It is proposed that GC analysts become 2 people, preparation analysts become 5 people, and the supervisor should be only 1 person. With this change in the number of workers, it is expected that the workload of each worker in the QC Department will be better, and work can be done more effectively, so that department productivity and process quality increase.